Penerapan Metode SMART Dalam Pemilihan Kelayakan Ayam Potong Bagi Peternak Ayam - Syahrian Syahrian; Dimas Mahendra (KLIK: Kajian Ilmiah Informatika dan Komputer, 2020)
The livestock sector in chickens is an option that can be filled in a chicken farm. Selection of a suitable type of chicken is from a chicken farm in order to get good quality. The purpose of this study was to suggest or care for the best chickens that were fit for slaughter using the SMART method. We obtained the data source by interview. And furthermore providing access to 4 types of chickens from one research site in our area in the village of like the earth, bamang hulu sub-district, East Kotawaringin district, the types of chickens used (alternatives), namely: turkey (A1), native chicken (A2), chicken kate (A3), Chicken Race (A4), the criteria we use are: Stock (K1), Price (K2), Quality (K3), and Size (K4). The results of our research conclude that turkey (A1) becomes the first recommended chicken with a value of 1 and native chicken becomes the second chicken (A2). One of the recommendations is the second recommended value of 0.426